Go backward to Multiple Variable BindingsGo up to TopGo forward to Sum Identities |

For all vars `i` and `j` and formulas `F`
(in which `j` does not occur freely), `G`
(in which `i` does not occur freely), and `H`
and terms `T` and `U`:

(sum_{i, F}T) * (sum_{j, G}U) = (sum_{i, F}(sum_{j, G}T*U)).

(sum_{i, F}(sum_{j, G}T)) = (sum_{j, G}(sum_{i, F}T)) = (sum_{i, j, F /\ G}T).

(sum_{i, F}T) + (sum_{i, H}T) = (sum_{i, F \/ H}T) + (sum_{i, F /\ H}T).

Author: Wolfgang Schreiner

Last Modification: November 16, 1999